Network-Generative Architecture a net-resilient paradigm for critical information infrastructure - Abes, Pocholo Alfonso M.; Gines, Leonido M. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
In the realm of architectural design for critical information infrastructure, there is a
noticeable gap in literature concerning the harmonious integration of human and
technological resilience. Existing studies predominantly emphasize the robustness of built
environments in withstanding shocks, overlooking the nuanced interplay between human
users, non-human equipment, and the surrounding ecological environment within an
architectural network. To address this gap, this research adopts an interdisciplinary approach,
drawing insights from data center experts and cybersecurity professionals in the Philippines.
Conducting interviews with key industry figures and performing site visits to existing data
center spaces, this research aims to understand the spatial needs and preferences of critical
infrastructure and knowledge workers. The findings from these engagements will be
systematically compared to models for resilient spaces, facilitating the adaptation of these
models to the unique context of the Philippines. The outcome will serve as the foundation for
designing an Information Shelter, integrating a colocation data center and a cybersecurity
research and development hub. This research argues that true resilience in critical
information infrastructure necessitates a holistic approach encompassing all elements within
the architectural network. Guided by Actor-Network Theory, the proposed design concept
seeks to establish a net-resilient paradigm, acknowledging the interconnectedness of human,
technological, and ecological components. The research contributes to the discourse on
spatial design principles crucial for fostering innovation and resilience in the face of evolving
threats, emphasizing the need for adaptable and interconnected built environments.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Architecture -- Computer-aided design -- Philippines; Computer security -- Philippines; Information superhighway -- Philippines; Resilience (Ecology) -- Philippines; Architecture -- Human factors -- Philippines; Actor -- Network Theory; Architecture and technology -- Philippines